1993
DOI: 10.1007/bf01103109
|View full text |Cite
|
Sign up to set email alerts
|

Alanine is a precursor in the biosynthesis of fumonisin B1 byFusarium moniliforme

Abstract: The biosynthesis of fumonisin B1 by Fusarium moniliforme was studied in liquid culture. Stable isotope labeled alanine was added as a precursor to static and shaken cultures of F. moniliforme. Incorporation of 13C and 2H labeled L-alanine into fumonisin B1 was measured by GC-MS. Under static culture conditions, 20.8 micrograms ml-1 of FB1 were produced with a 5.5% level of incorporation of intact, labeled alanine into fumonisin B1. Under shake culture conditions, much higher levels of fumonisin B1 were produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 16 publications
3
49
0
3
Order By: Relevance
“…The label from C-3 of alanine was incorporated into C-1 of fumonisin in agreement with previous studies (14). However, alanine was also catabolized as evidenced by the labeling of the even positions of the backbone and the ester functions, although to a lesser extent.…”
Section: Biosynthesis Of Fbsupporting
confidence: 90%
See 1 more Smart Citation
“…The label from C-3 of alanine was incorporated into C-1 of fumonisin in agreement with previous studies (14). However, alanine was also catabolized as evidenced by the labeling of the even positions of the backbone and the ester functions, although to a lesser extent.…”
Section: Biosynthesis Of Fbsupporting
confidence: 90%
“…Past studies have shown the advantage of incorporating specifically enriched 13 carbon (C)-acetate into fungal cultures at the appropriate time of biosynthesis of a particular metabolite as a preliminary step to preparing radiolabeled ( 14 C) compounds for toxicologic research (11,12). The 13 C studies permit determination of the most cost-effective method to manufacture highly enriched 14 C-FB 1 labeled in multiple locations for use in radiotracer studies. An earlier study has shown that the 13 C-acetate is incorporated into the fumonisin backbone in a manner more suggestive of polyketide biosynthesis than of lipid biosynthesis, but the analyses were performed on impure FB 1 (13).…”
Section: Biosynthesis Of Fbmentioning
confidence: 99%
“…The fumonisin B (FB) analogs, comprising toxicologically important FB 1 , FB 2 , and FB 3 , are the most abundant naturally occurring fumonisins, with FB 1 predominating and usually being found at the highest levels (36). FB 1 typically accounts for 70 to 80% of the total fumonisins produced, while FB 2 usually makes up 15 to 25% and FB 3 usually makes up from 3 to 8% when cultured on corn or rice or in liquid medium (7,39,40). Apart from the FB series, some of the other analogs may occur in naturally contaminated maize at relatively low levels (Ͻ5% of the total fumonisins present) (48).…”
Section: Fumonisin Analogsmentioning
confidence: 99%
“…The fumonisin B (FB) analogs, comprising toxicologically important FB1, FB2, and FB3, are the most abundant naturally occurring fumonisins, with FB1 predominating and usually being found at the highest levels [96] in feed ingredients and poultry feed in world wide. FB1 accounts for about 80% of the total fumonisins produced inthis substrates, while FB2 usually makes around 20% and FB3 usually makes up from about 5% when cultured on corn or rice or in liquid medium [97][98][99][100].…”
Section: Aetiologymentioning
confidence: 99%